Implementasi Sistem Penyiraman Otomatis Berbasis Arduino Pada Lahan Pertanian Gabungan Kelompok Tani Mekarjaya - Yanti Yanti; Abd Rohman; Siti Maesaroh; Asep Mustopa; Rizki Muh Febrian; Rika Rahmawati; Mochamad Fachry Ridwan (LPPM Universitas Harapan Bangsa Purwokerto, 2023)
Indonesia is a nation of farmers with very fertile soil conditions and abundant natural resources. Most of the land is used for plantations and agriculture. Regulation of the flow of water or irrigation on agricultural land is an important factor affecting agricultural production. This community service aims to implement an arduino-based irrigation system automation for water spinach plants on agricultural land of Mekarjaya Farmer Group Association in Cikupa Village. This automation system is an irrigation system in water spinach farming by turning on the water pump based on the specified time and and turning off the water pump based on the degree of soil moisture measured by the soil moisture sensor. The implementation method is carried out by providing education to farmers who are members of Mekarjaya Farmer Group Association in Cikupa Village through several series of activities including the stages of preparation, outreach, making of an automatic sprinkler system, mentoring, and evaluating results. Arduino-based automatic sprinkler system can control and do irrigation automatically on water spinach plants. The results of the implementation of an Arduino-based automatic sprinkler system on agricultural land of Mekarjaya Farmer Group Association in Cikupa Village show that the water spinach plants have been successful in growing and can be harvested